Resilience is low in adolescents with asthma and independent of asthma control. - Ciprandi, Giorgio; Marseglia, Gian Luigi; Licari, Amelia; Castagnoli, Riccardo; Ciprandi, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
N/A